THE DEVELOPMENT AND IMPLEMENTATION OF SYSTEM INFORMATION MANAGEMENT “LABSAINS 1.0" FOR SUPPORTING PRACTICUM ACTIVITIES IN FTIK LABORATORY AT IAIN PONOROGO - Dzukha Asyiqin, Akbar; Mudhofar, Moh.; Wijaya, Buana Handa (INSECTA: Integrative Science Education and Teaching Activity Journal, 2025)
The controlling record data for the FTIK laboratory at IAIN Ponorogo relies on conventional methods. These methods have encountered several challenges. The inventory recording of the laboratory, reagents, and scheduling is conducted through manual entries in a notebook. The management of these methods presents multiple challenges. This research aims to develop a laboratory management information system to address the problem of laboratory service efficiency at FTIK IAIN Ponorogo.  Optimization of laboratory management in supporting student activities is carried out through a management information system. The development of the "LabSains 1.0" system at the FTIK Laboratory is the first pilot project for laboratory digitization within IAIN Ponorogo. The system development uses the waterfall method to follow the systematic flow needed in software creation. The operational efficiency results of using the “LabSains 1.0" system reach a moderate rate at a ratio of 74%. This study focuses on three main efficiency indicators, including enhancing service quality, reducing errors in the organization, and increasing user satisfaction.  86% of students stated strongly agree with the use of the system in the laboratory. The professional development and implementation of “LabSains 1.0" systems have improved laboratory competitive services.  These organizing activities can provide benefits through an automated system that features comprehensive document processing capabilities.